Methylation of insulin DNA in response to proinflammatory cytokines during the progression of autoimmune diabetes in NOD mice - Rui, Jinxiu (Diabetologia, 2016)
AIMS/HYPOTHESIS: Type 1 diabetes is caused by the immunological destruction of pancreatic beta cells. Preclinical and clinical data indicate that there are changes in beta cell function at different stages of the disease, but the fate of beta cells has not been closely studied. We studied how immune factors affect the function and epigenetics of beta cells during disease progression and identified possible triggers of these changes. METHODS: We studied FACS sorted beta cells and infiltrating lymphocytes from NOD mouse and human islets. Gene expression was measured by qRT-PCR and methylation of the insulin genes was investigated by high-throughput and Sanger sequencing. To understand the role of DNA methyltransferases, Dnmt3a was knocked down with siRNA. The effects of cytokines on methylation and expression of the insulin gene were studied in humans and mice. RESULTS: During disease progression in NOD mice, there was an inverse relationship between the proportion of infiltrating lymphocytes and the beta cell mass. In beta cells, methylation marks in the Ins1 and Ins2 genes changed over time. Insulin gene expression appears to be most closely regulated by the methylation of Ins1 exon 2 and Ins2 exon 1. Cytokine transcription increased with age in NOD mice, and these cytokines could induce methylation marks in the insulin DNA by inducing methyltransferases. Similar changes were induced by cytokines in human beta cells in vitro. CONCLUSIONS/INTERPRETATION: Epigenetic modification of DNA by methylation in response to immunological stressors may be a mechanism that affects insulin gene expression during the progression of type 1 diabetes.